Faculty Policy Management in Improving Accreditation: A Study of Three Leading Study Programs at IAIN Ternate - Annisah Naela Pake; Minggusta Juliadarma; Ramli Yusuf (Manunggal Halim Jaya, 2026)
Study program accreditation is a key indicator of higher education quality and requires systematic and sustainable policy management. This study aims to analyze the policy management of the Faculty of Islamic Education and Teacher Training (FTIK) of IAIN Ternate to improve the accreditation of superior study programs. The study used a light mixed methods approach with data collection techniques in the form of accreditation document studies, in-depth interviews with faculty leaders and study program heads, and strengthening descriptive quantitative data related to accreditation. The results show that planned, collaborative, and quality-oriented faculty policies play a significant role in improving the accreditation status of the Islamic Education Management Study Program, Islamic Religious Education, and Madrasah Ibtidaiyah Teacher Education programs. These policies are implemented through intensive mentoring, strengthening the culture of quality, and integrating Islamic education management values. This study confirms that the faculty is a strategic actor in the quality assurance system and accreditation improvement in Islamic higher education.